The Model Latihan untuk Meningkatkan Keterampilan Pukulan Backhand Tenis Meja pada Mahasiswa : A Systematic Literature Review: Tinjauan Literatur Sistematis - Garry William Dony; Yudo Harvianto; Cahyo Nugroho Sigit (Jurnal Porkes, 2026)
Table tennis requires a comprehensive mastery of basic techniques, with the backhand stroke often considered more complex than the forehand. A preliminary study of 55 college students showed that backhand proficiency (58.2%) was lower than that of the forehand (78.2%), with difficulties in accuracy, coordination, body position, and consistency. This systematic literature review (SLR) aims to identify, analyze, and evaluate effective training models for improving table tennis backhand skills among college students. Following the PRISMA 2020 guidelines, a literature search was conducted in the Google Scholar, PubMed, ScienceDirect, and Scopus databases for articles published between January 2020 and March 2026, yielding 18 articles from 847 identified records. The review identified six effective training models: (1) multi-ball drills, (2) partner drills, (3) goal-based training, (4) external attention-based training, (5) digital technology-based training, and (6) sports education models. The principle of analogy from other sports, such as volleyball and futsal, also supports the implementation of structured training and target-based patterns. A combined training model that integrates technical variations, immediate feedback, and structured repetition has been shown to provide optimal results for students. These findings provide evidence-based guidance for designing backhand training programs in higher education settings.